Organ-sparing treatment for breast cancer - E. A. Rasskazova; A. D. Zikiryakhodzhaev; A. D. Kaprin (Опухоли женской репродуктивной системы)
This article reviews literature on organ-sparing and oncoplastic surgeries for breast cancer. Initially, we performed organ-sparing surgeries in patients with stage I—IIA breast cancer and then compared outcomes with those in patients after radical mastectomy. Since there were no differences in both overall and relapse-free survival between the groups, we started to perform organ-sparing surgeries in women with locally advanced breast cancer after neoadjuvant therapy who achieved complete or partial response. Oncoplastic resections were used to achieve good aesthetic results and also for patients in whom classical organ-sparing resection would inevitably result in a poor cosmetic outcome due to the tumor location. In recent years, the technique of extreme oncoplastic breast resection has emerged as a promising option that extended the scope of indications to organ-sparing treatment. In particular, it allows breast conservation for patients with multicentric, multifocal tumors, and tumors >50 mm. All organ-sparing and oncoplastic operations first of all improve the quality of life of breast cancer patients.